2022
DOI: 10.1177/00332941221109119
|View full text |Cite
|
Sign up to set email alerts
|

Dark Triad Personality and Phubbing: The Mediator Role of Fomo

Abstract: Phubbing among undergraduate has become an area of increasing research interest in recent years. In recent years, studies on phubbing have increased. However, no empirical study has deal with the mediating effect of fear of missing out (FoMO) on the relationship between dark triad and phubbing. The dark triad refers to three personality traits: Machiavellianism, psychopathy, and narcissism. Machiavellianism is characterized by prioritizing one’s own wishes and desires. Psychopathy, is a personality trait where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…This aligns with research suggesting that FoMO mediates the association between personality characteristics and phubbing (e.g. 30 ). The present results provide novel insights into how the association between DoS and FoMO impacts the misuse of social media (i.e., phubbing), suggesting that uncertainties about interpersonal relationships can intensify apprehension about missing out on opportunities, motivating a heightened reliance on social media to alleviate such unease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This aligns with research suggesting that FoMO mediates the association between personality characteristics and phubbing (e.g. 30 ). The present results provide novel insights into how the association between DoS and FoMO impacts the misuse of social media (i.e., phubbing), suggesting that uncertainties about interpersonal relationships can intensify apprehension about missing out on opportunities, motivating a heightened reliance on social media to alleviate such unease.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of phubbing varies depending on such factors as age, education level, and cultural context. Overall, research suggests that phubbing is a widespread behavior that can have negative consequences on relationships and mental health 30 . Such behavior will likely erode couple dynamics, leaving individuals feeling undervalued 31 .…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that FoMO probably originated from social media, which agreed with the majority of FoMO research studies. Previous studies predominantly characterized FoMO as the constant need for up-to-date information and highlighted its close association with the frequency of social media usage (Alutaybi et al, 2020;Li, 2020;Perna, 2020;Scheinfeld & Voorhees, 2022) and problematic behaviors related to social media (Akat et al, 2022;Ergin & Karataş, 2022;Shen et al, 2020). Nevertheless, a contrasting perspective emerged from research conducted by Hamutoglu et al (2020), suggesting that daily social media engagement did not significantly predict FoMO.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly defined as the fear of not being immediately updated with trending information (Alutaybi et al, 2020), leading to a habit of constantly checking social media. This phenomenon has been identified as a significant factor contributing to social media addiction (Shen et al, 2020), as well as other problematic social media habits like phubbing (Akat et al, 2022) and cyberloafing (Ergin & Karataş, 2022). FoMO is not only a consequence of social media usage; it has also been associated with social media-related issues, such as social appearance anxiety (Ergin & Karataş, 2022) and excessive social media frequency and engagement (Li, 2020;Scheinfeld & Voorhees, 2022).…”
Section: Fomo and Social Mediamentioning
confidence: 99%
“…Pitifully, most previous studies on phubbing mainly focused on its adverse consequences, while only limited research has revealed the potential determinants (Garrido et al, 2021). The previous studies concerning antecedents of phubbing reveal that boredom (Doumit et al, 2023;Lv & Wang, 2023), depression (Sun & Samp, 2021), narcissism (Akat et al,2022;Grieve & March, 2020), parental psychological aggression (Gao et al, 2022), and parental phubbing (Liu et al, 2022) can predict phubbing positively, while open-mindedness (Doumit et al, 2023) and agreeableness (Sun & Samp, 2021) can predict phubbing negatively. However, an important risk factor, social anxiety, has been largely ignored from previous studies.…”
Section: Introductionmentioning
confidence: 99%